Adapting roughages varying in quality and curing processes to the nutrition of beef cattle. Combinations of wheat straw and alfalfa hay in the winter ration of beef heifers. - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Previous work at this station (Circular 297. p. 45-47) and at the Fort Hays Branch Experiment Station (Circular 322, p. 1-6) indicates that beef calves wintered on a daily ration of 1.75-2 pounds of ground sorghum grain, 1.25-2 pounds of protein concentrate and wheat straw fed free-choice made average daily gains of only .3 to .6 pound. One pound of molasses substituted for 1 pound of grain and sprinkled on wheat straw increased consumption only .22 pound per head dally but decreased gains .08 pound per head dally. Also 1 pound of molasses had slightly less feeding value than 1 pound of grain in a wintering ration for steer calves with wheat straw roughage. The addition of 1 pound of dehydrated alfalfa pellets increased the rate of gain and feed efficiency. Calves receiving dehydrated alfalfa pellets also consumed more straw.
Keywords: Beef; Curing process; Nutrition; Feed efficiency